Benefits of Mother–Baby Skin-to-Skin Contact. Issue 3 (May 2022) - Spatz, Diane L.
Abstract : Skin-to-skin contact has numerous benefits for newborns including supporting breastfeeding. Our breastfeeding expert, Dr. Spatz, reviews some of the most recent systematic reviews and meta-analyses on skin-to-skin contact and offers suggestions for improving rates on maternity units.